2003
DOI: 10.1016/s0002-9440(10)63921-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Interaction between CCR1 and Its Ligand, CCL3, Induced by Endogenously Produced Interleukin-1 in Human Hepatomas

Abstract: Hepatoma cell lines can produce a massive amount of chemokines in response to various stimuli including hepatitis viruses and their products. However, it remains elusive on the types of chemokine receptor(s) expressed in the hepatoma tissues and its roles in hepatoma development. To clarify these points, we examined the chemokine receptor expression in six human hepatoma cell lines. All of the hepatoma cell lines constitutively and exclusively expressed CCR1 mRNA and its protein on their cell surface. CCR1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 48 publications
3
65
0
Order By: Relevance
“…We previously demonstrated that a chemokine, CCL3, was abundantly expressed in human hepatocellular carcinoma tissues and proved the crucial involvement of CCL3 and its receptor, CCR1, in chemical carcinogen-induced murine hepatocarcinogenesis (39). Our preliminary experiments demonstrated that i.v.…”
Section: Discussionmentioning
confidence: 60%
“…We previously demonstrated that a chemokine, CCL3, was abundantly expressed in human hepatocellular carcinoma tissues and proved the crucial involvement of CCL3 and its receptor, CCR1, in chemical carcinogen-induced murine hepatocarcinogenesis (39). Our preliminary experiments demonstrated that i.v.…”
Section: Discussionmentioning
confidence: 60%
“…Likewise, human hepatocellular carcinoma (HCC) cells express CCR1 and its ligands can reduce the proliferation of human HCC cell lines [33].…”
Section: Direct Effects On Cancer Cellsmentioning
confidence: 99%
“…After treating the RNA preparations with RNasefree DNase I (Qiagen) to remove residual DNA, cDNA was synthesized as described previously (19). Quantitative realtime PCR was done on a StepOne Real-Time PCR System (Applied Biosystems) using the comparative C T quantification method.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%